Preliminary Study Of Dicalcium Phosphate Dihydrate Coated 45S5 Bioglass Granule - Gan, Soon Xin (Universiti Sains Malaysia, 2022)
In this study, dicalcium phosphate dihydrate (DCPD) which has higher solubility is being coated on the 45S5 bioglass granule surface to improve the bone regeneration rate. The objectives of this preliminary study are to determine the effect of acidic calcium phosphate solution concentration in fabricating dicalcium phosphate diphosphate (DCPD) coated 45S5 bioglass granules and its effect of exposure duration when soaking in acidic calcium phosphate solution. 45S5 bioglass is first fabricated by using melt-quench method and the fabricated 45S5 bioglass is verified through morphology observation, elemental analysis and compositional analysis. To achieve the first objective, 45S5 bioglass granules was exposed to acidic calcium phosphate solution with different concentration (25 mmol/L, 50 mmol/L, 75 mmol/L, 100 mmol/L) for 2 hours to form a DCPD layer on the 45S5 bioglass granule surface through dissolution-precipitation reaction. While for the second objectives, the concentration of acidic calcium phosphate was fixed at 100mmol/L and 45S5 bioglass granules were soaked in the solution for 2 and 6 hours, respectively. The DCPD-coated 45S5 bioglass are then characterized with Scanning Electron Microscope (SEM), X-Ray Fluorescence Spectroscopy (XRF), X-ray Diffractometer (XRD) and pH analysis. The results showed that the amount of DCPD crystals precipitate on the 45S5 bioglass granule surface increased as the concentration of ACaP solution and exposed duration increased. In this study, even the DCPD is detected to be precipitated on the 45S5 bioglass granule surface, the results has shown that the DCPD precipitated is not fully covered the 45S5 bioglass granule surface and further study is required to understand the appropriate method to fully cover the 45S5 bioglass granules surface with DCPD.